2008
DOI: 10.1177/1934578x0800300304
|View full text |Cite
|
Sign up to set email alerts
|

Myrsicorianol, A New Prenylated Benzoic Acid Derivative from Myrsine Coriacea

Abstract: A new prenylated benzoic acid derivative, named myrsicorianol (1), was isolated from the fruits of Myrsine coriacea and its structure was determined by spectral analysis, including 1D-and 2D-NMR experiments. Myrsinoic acid A and a mixture of the p-benzoquinones, embelin, rapanone and 2,5-dihydroxy-3-pentadecyl-1,4-benzoquinone (homorapanone) were also obtained from the fruits, whilst the bark afforded myrsinoic acid A, myrsinoic acid B, 3-(3',7'-dimethyl-2',6'-octadienyl)-4hydroxybenzoic acid and 3-(3',7'-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In the intervening period, MA-F and its various cometabolites, which can also be obtained from certain other plant sources, have been identified as HB-EGF inhibitors (and hence represent potential anticancer agents), as key elements of formulations for treating halitosis, as antimicrobial agents, and as compounds with notable antileishmanial properties . Given these pronounced activities and the absence of studies on the preparation of any cyclic members of the myrsinoic acid class, we sought to prepare compound 1 .…”
mentioning
confidence: 99%
“…In the intervening period, MA-F and its various cometabolites, which can also be obtained from certain other plant sources, have been identified as HB-EGF inhibitors (and hence represent potential anticancer agents), as key elements of formulations for treating halitosis, as antimicrobial agents, and as compounds with notable antileishmanial properties . Given these pronounced activities and the absence of studies on the preparation of any cyclic members of the myrsinoic acid class, we sought to prepare compound 1 .…”
mentioning
confidence: 99%
“…Additionally, the presence of two monoprenylated benzoic acid derivatives ( 13 and 14 ) was already reported for the related species Eriodictyon sessilifolium (Figure ). Prenylated benzoic acid derivatives are secondary metabolites, which are not widely distributed in nature . The biological activities of this class of compounds include anti-inflammatory , antifungal , antimicrobial , and antioxidative properties , .…”
Section: Resultsmentioning
confidence: 99%
“…NMR Analysis. 1 H, 13 C NMR, and 2D NMR spectra were acquired with an Avance III 600 MHz NMR spectrometer (Bruker). The NMR spectra were recorded in DMSO-d 6 referenced to residual solvent signals with resonances at δ H 2.49/δ C 39.5 ppm.…”
Section: ■ Methodsmentioning
confidence: 99%
“…During phytochemical analysis of Campylotropis hirtella , it was revealed that flavonoids with a prenyl group have higher antibacterial activities than the parent compounds, probably because these groups heighten lipophilicity and confer to the molecule a strong affinity for biological membranes . Among plant sources, the prenylated benzoic acid derivatives from Piper species are a source of anti-infective agents and exhibit antiherbivore activity …”
mentioning
confidence: 99%